Intra- and inter-brain coupling and activity dynamics during improvisational music therapy with a person with dementia: an explorative EEG-hyperscanning single case study - Maidhof, Clemens; Müller, Viktor; Lartillot, Olivier; Agres, Kat; Bloska, Jodie; Asano, Rie; Odell-Miller, Helen; Fachner, Jörg (Frontiers in Psychology, 2023)
Real-life research into the underlying neural dynamics of improvisational music therapy, used with various clinical populations, is largely lacking. This single-case study explored within-session differences in musical features and in within- and between-brain coupling between a Person with Dementia (PwD) and a music therapist during a music therapy session. Dual-EEG from a music therapist and a PwD (male, 31 yrs) was recorded. Note density, pulse clarity and synchronicity were extracted from audio-visual data. Three music therapists identified moments of interest and no interest (MOI/MONI) in two drum improvisations. The Integrative Coupling Index, reflecting time-lagged neural synchronization, and musical features were compared between the MOI and MONI. Between-brain coupling of 2 Hz activity was increased during the MOI, showing anteriority of the therapist’s neural activity. Within-brain coupling for the PwD was stronger from frontal and central areas during the MOI, but within-brain coupling for the therapist was stronger during MONI. Differences in musical features indicated that both acted musically more similar to one another during the MOI. Within-session differences in neural synchronization and musical features highlight the dynamic nature of music therapy. The findings contribute to a better understanding of social and affective processes in the brain and (interactive) musical behaviors during specific moments in a real-life music therapy session. This may provide insights into the role of such moments for relational-therapeutic processes.